Solanum okadae - A wild diploid potato species with the potential to improve cultivated potato - Hundare, Amar (2023)
Crop breeding is critical for the production of high-quality food and, as a result, for increasing global food security. The cultivated potato (Solanum tuberosum) is the world's most important tuber crop and the fourth most important crop farmed for human consumption, is a prime candidate crop for addressing global food security. Wild potato species are a significant source of genes for novel traits and resistances to abiotic and biotic stresses that are lacking from most commercial cultivars. Diploid potatoes account for over 70% of wild and landrace potato species, and their tremendous diversity has not been properly defined or fully utilised in past breeding projects. Solanum okadae is one such wild diploid potato species from western Bolivia that has not been extensively studied.